ASUHAN KEPERAWATAN KELUARGA PADA TAHAP PERKEMBANGAN KELUARGA LANJUT USIA DI PUSKESMAS GONDANGREJO KARANGANYAR - Qomariyah, Annisa Nurul; Mardiyah, Siti (Journal of Advanced Nursing and Health Sciences, 2021)
Elderly is part of the human development process. A person is said to be elderly when he is more than 65 years old, at this time a person will generally experience gradual physical, mental and social decline. Hypertension is one of the common diseases suffered by the elderly. One technique that combines relaxation and regular physical activity that is used to treat hypertension in the elderly is to pray dhuha prayer. Dhuha prayer can act as physical health therapy and help the heart work properly. The case study design used by the author is descriptive observational by approaching and exploring case studies in patients with hypertension. Data were collected by interview, observation, and documentation study. The results of nursing care management during 4 home visits showed a decrease in blood pressure from 160/100 mmHg down to 140/80 mmHg. Giving the action of the dhuha prayer movement can have a positive impact on reducing blood pressure in clients and can be used as an intervention in family nursing care with hypertension health problems.